FERMENTASI PADAT DARI BEBERAPA LIMBAH LIGNOSELULOSA - Tjutju Nurhayati Syahri; Sri Komarayati; Gusailina Gusailina (Jurnal Penelitian Hasil Hutan, 1989)
Lignocellulosic     wastes  such  as  rubber  wood  saw  dust,   bagasse,   cayuput   oil  waste,  municipal  solid  waste,   vegetable waste  were  digested   by  solid  state  fermentation    at Thermophillic   temperature    (55°C),  and dry  matter  condition   of 20-40Percent  in 25 liter anaerobic   fermentors.All  of  the  lignocellulosic   wastes,   except  for cayuput   oil waste  can be digested.   The  result  revealed  that  the  biogas productivity   is about   1.66.5   V/V.r.d,   methane   content   about  48.853.3    percent,   retention   time  about   1334    days and efficiency   of  conversion  about   12-61 percent.Solid  state   fermentation    at  the  above  mentioned    conditions   increases  the  biogas productivity     of  about  2-6   times more  than  that  of  the  conventional    method.Solid  state  fermentation   of  a mixture  of  rubber  wood  saw dust and water hyacinth   (ratio  90/10) revealed that  bioga» productivity   was the  lowest,   retention  time  appeared  to be the longest and the efficiency of  conversion  was relatively  low (15%),,    On the  other  hand,  solid  state   fermentation    of  fresh  municipal  solid  waste gave  the  highest  productivity    of about 6.5 V/V,r,d,  relatively short retention  time  (16.6  days) and high efficiency  of about  57%.  Solid  state  fermentation   of  mixture of  rice straw and  water hyacinth   (95/5)  and  also of  the municipal  solid waste,  rubber  wood  saw dust,  bagasse and water hya- cinth  (68/ 15/ 1214) gave   a high productivity    and  efficiency.